The effect of compulsory face mask policies on community mobility in Germany - Kovacs Roxanne; Dunaiski Maurice; Tukiainen Janne (Wiley (Commercial Publisher), 2025)
There is an ongoing debate about making face masks compulsory in public spaces to contain COVID-19. A key concern is that such policies could undermine efforts to maintain social distancing and reduce mobility. We provide first evidence on the impact of compulsory face mask policies on community mobility. We exploit the staggered implementation of policies by German states during the first wave of the pandemic and measure mobility using geo-located smartphone data. We find that compulsory masking policies led to a short-term reduction in community mobility, with no significant medium-term effects. We can rule out even small increases in mobility.